2009
DOI: 10.2754/avb200978030399
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Lupine in the Diets for Pigs (a Review)

Abstract: The seeds of sweet lupine cultivars (Lupineus species) have been used with increasing frequency as a source of proteins replacing proteins of animal origin or soybean in feed compounds. The seeds of sweet lupine cultivars contain an average of about 33-40% crude protein in dry matter, the lipid content ranges from 5 to 13%. The profile of amino acids is relatively beneficial, however, with slightly lower content of lysine (1.46%) and methionine (0.22%). The main storage carbohydrates in the seeds are the β-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…is partly due to the low level of starch, which is replaced by fat as the main energy source. As expected, lupine seeds showed more dietetically beneficial structural carbohydrates (NDF 242 g kg −1 DM) compared with other leguminous seeds (peas, faba beans, soy beans); this fraction is mainly represented by pectin‐like material . The ME value, estimated from chemical and gas production data, differed slightly between seeds (mean 14.5 ± 0.60 MJ kg −1 DM).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…is partly due to the low level of starch, which is replaced by fat as the main energy source. As expected, lupine seeds showed more dietetically beneficial structural carbohydrates (NDF 242 g kg −1 DM) compared with other leguminous seeds (peas, faba beans, soy beans); this fraction is mainly represented by pectin‐like material . The ME value, estimated from chemical and gas production data, differed slightly between seeds (mean 14.5 ± 0.60 MJ kg −1 DM).…”
Section: Resultsmentioning
confidence: 61%
“…As expected, lupine seeds showed more dietetically beneficial structural carbohydrates (NDF 242 g kg −1 DM) compared with other leguminous seeds (peas, faba beans, soy beans); this fraction is mainly represented by pectin-like material. 40 The ME value, estimated from chemical and gas production data, differed slightly between seeds (mean 14.5 ± 0.60 MJ kg −1 DM). It is necessary to underline that, in ME calculation, fat and fiber levels as well as other nutrient availability have a negative influence on microorganism activity in the rumen and consequently on in vitro fermentation.…”
Section: Chemical Compositionmentioning
confidence: 91%
“…As regards white lupin of Amiga variety, the authors (Zralý et al 2008;Písaříková and Zralý 2009) found out a fat content of 107.7 g/kg. In Butan variety, the content in a whole or dehulled seed is 79.1 and 102.3 g/kg of dry matter.…”
Section: Fats and Fatty Acidsmentioning
confidence: 99%
“…It contains 33-40 % of crude protein and 5-13 % oil. 4,5 In Egypt, the productivity of 1482 ha cultivated with lupine is 2881 tons (19, 439 kg/ha). 6 The productivity of lupine remains low due to physiological, biological and environmental stress factors.…”
Section: Introductionmentioning
confidence: 99%